Mengenal Tanda-Tanda Bahaya Kehamilan di Puskesmas Pakuan Baru Kota Jambi - Ria Febrina (Jurnal Abdimas Kesehatan (JAK), 2021)
Maternal Mortality Rate (MMR) in Indonesia is still high compared to other ASEAN countries. MMR in Indonesia according to the 2017 Indonesian Demographic and Health Survey (IDHS) is 305 per 100,000 live births. The global target of SDGs (Suitainable Development Goals) is to reduce the Maternal Mortality Rate (MMR) to 70 per 100,000 live births. While in Jambi Province in 2017 recorded maternal deaths were 29 cases. Maternal deaths that occur during 90% of pregnancy are caused by obstetric complications. Direct obstetric complications are bleeding, infection and eclampsia. Indirectly maternal mortality is also influenced by delays at the family level in recognizing danger signs of pregnancy and making decisions to immediately seek help. Delay in reaching health facilities and assistance in health service facilities. Pregnancy danger signs must be recognized and detected early so that they can be handled properly because any danger signs of pregnancy can lead to pregnancy complications. Therefore it is necessary to provide counseling to improve the knowledge of pregnant women about the danger signs of pregnancy. This community service activity was carried out by Pakuan Baru Kota Jambi Public Health Center. The time of implementation in April 2020. The target is pregnant women. Community service methods include a survey and lecture approach. The results obtained are pregnant women able to understand the danger signs of pregnancy. It is recommended for health workers to continue to provide education related to pregnancy to pregnant women